PRELIMINARY STUDY OF HYDROGEN PRODUCTION FROM ALUMINIUM CORROSION REACTION IN ALKALINE SOLUTION - Fata Alhadi, Muhammad
The utilization of fossil fuels as an energy source has a detrimental impact on global warming, making hydrogen-based energy systems a highly promising alternative. Among the many metals capable of producing hydrogen, aluminum stands out due to its outstanding electron density and oxidation potential. This study aims to produce hydrogen from solid aluminum powders and aluminum spheres via alkaline hydrolysis method using a laboratory-scale artificial hydrogen reactor. The impact of various reaction parameters, such as electrolyte concentration and the weight and size of the aluminum, on the efficiency of hydrogen gas production was investigated. A series of experiments were conducted to produce hydrogen through alkaline hydrolysis at different NaOH concentrations, such as 0.5 M, 0.75 M, and 1 M, at the same temperature and volume of electrolyte solution. The aluminum spheres were 5 mm and 8 mm in diameter, and the aluminum powder size was -325 mesh. Meanwhile, the aluminum weight variations were 1 g, 2 g, and 3 g. Each batch of the hydrogen gas production experiment lasted for 30 minutes. The ANOVA and Taguchi method determined the optimum parameters for hydrogen gas production by analyzing the interaction between parameters based on the obtained data. Gas Chromatography (GC) analysis was performed to confirmed hydrogen content in the produced gas. The performance evaluation of the hydrogen production process was based on the results obtained from the experiment. ANOVA results showed that the three variables used had a significant effect, except for the interaction between size variation and weight. The aluminum size factor gave the highest contribution of 66%. The optimum condition that gave the highest rate of hydrogen gas production, reaching 1000 mL in 96 seconds, was achieved with a 1 M of NaOH concentration and 3 grams of aluminum powder with a size of -325 mesh. Gas Chromatography analysis shows that the composition of the gas produced from the aluminum ball sample consists of 94% hydrogen gas and 6% nitrogen gas, while the aluminum powder sample produces 100% hydrogen gas.The volume of hydrogen gas tend to increase with decreasing size and increasing weight and electrolyte concentration.